INSECTS FOUND IN FUNERAL BUNDLE FROM THE TOPATER ARCHAEOLOGIC CEMETERY (REGION OF ATACAMA, CHILE) (Acta Entomológica Chilena, 2022)
It is documented and discussed the finding of insects within a “funeral bundle” from the Topater archaeologic cemetery (Atacama, Calama’s province), that are dated by termoluminescence between 1.025 ± 100 a 2.630 ± 260 years before present (B.P.). It was found the presence of Dermestes peruvianus and Anthrenus sp. (Coleóptera, Dermestidae), together with Tineidae (Lepidoptera) and puparium of two species of Sarcophagidae (Díptera). It is concluded that coleóptera carne from the bundle post storage. Instead, the Sarcophagidae are contemporaneous with the mommies of funeral bundles coming from the post mortem decomposition.
Keywords: Funeral Bundle, Archeology, Dermestidae, Tineidae, Sarcophagidae, Chile